Body weight in patients with idiopathic gastroparesis. Issue 2 (15th September 2020) - Parkman, Henry P.; Van Natta, Mark; Yamada, Goro; Grover, Madhusudan; McCallum, Richard W.; Sarosiek, Irene; Farrugia, Gianrico; Koch, Kenneth L.; Abell, Thomas L.; Kuo, Braden; Miriel, Laura; Tonascia, James; et al.
Abstract: Background: The classic clinical picture of gastroparesis is a symptomatic patient losing weight. In addition, a number of patients with delayed gastric emptying are obese and/or gaining weight. Our aim was to investigate the factors impacting body weight in patients with idiopathic gastroparesis. Methods: In patients with idiopathic gastroparesis, detailed history and weight were acquired at enrollment and after 48 weeks. Questionnaires assessed symptoms, food intake, physical activity, and quality of life. Patients underwent laboratory testing, gastric emptying scintigraphy, and water load testing. Results: Of 138 patients with idiopathic gastroparesis, 10% were underweight (BMI < 18.5), 39% were normal weight (BMI 18.5‐25), 20% were overweight with BMI 25 to 30 kg/m 2, and 29% were obese with BMI > 30 kg/m 2 . Body weight at enrollment was positively associated with oral caloric consumption ( P  < .001), following a gastroparesis diet ( P  = .04), nutrition consultation ( P  = .001), upper abdominal pain ( P  = .01); and negatively associated with energy expenditure ( P  = .05), alcohol use ( P  = .003) and severity of bloating ( P  < .001). When followed over 48 weeks, 53% patients stayed stable (within 5% of baseline weight), 30% gained, and 17% lost weight. Weight gain over 48 weeks was positively associated with oral caloric consumption ( P  = .003) and constipation severity ( P  = .005) at enrollment, and negatively associated with lower abdominal pain severity ( P  = .007) at enrollment, and associated with improvement in inability to finish meal score ( P  < .001) at 48 weeks. Conclusions: In this series of patients with idiopathic gastroparesis, 10% were underweight whereas 29% were obese. Over 48 weeks, 30% of patients increased their body weight ≥ 5%. Diet, activity, and symptoms are important factors associated with body weight in patients with idiopathic gastroparesis. Abstract : In this series of patients with idiopathic gastroparesis, 10% were underweight whereas 29% were obese. Diet, activity, and symptoms are important factors associated with body weight in patients with idiopathic gastroparesis.